Integrating social activity theory and critical discourse analysis: a multilayered methodological model for examining knowledge mediation in mentoring. Issue 4 (20th April 2016) - Becher, Ayelet; Orland-Barak, Lily
Abstract : This study suggests an integrative qualitative methodological framework for capturing complexity in mentoring activity. Specifically, the model examines how historical developments of a discipline direct mentors' mediation of professional knowledge through the language that they use. The model integrates social activity theory and a framework of critical discourse analysis to guide the data collection, analysis and interpretation processes. Drawing on the case of mentoring in Arts Education, we describe and discuss the discursive character of the interactions between content and pedagogy in mentoring activity, as they grow out of the larger historical groundings of participants' practice.